Comparative study of epidural xylazine or clonidine in horses - Doria, Renata G. S. [UNESP]; Valadao, Carlos A. A. [UNESP]; Duque, Juan C. [UNESP]; Farias, Anderson [UNESP]; Almeida, Ricardo M. [UNESP]; Netto, Augusto Castro (Blackwell Publishing, 2008)
Objective To evaluate the cardiorespiratory and behavioural effects of epidural xylazine (XYL) or clonidine (CLO) in horses.Study design Blinded, randomized experimental study.Twelve healthy Arabian yearling horses weighing 117-204 kg were randomly allocated into two groups: XYL (n = 6) and CLO (n = 6).Methods An epidural catheter was inserted and a facial arterial catheter was placed and the next day the horses were restrained in stocks. Baseline values for heart (HR) and respiratory (RR) rates, arterial pressure and behavioural responses were evaluated before (TO) and 10, 20, 30, 45, 60, 90 and 120 minutes after epidural injection (T10-T120). The horses received 0.2 mg kg(-1) of XYL or 5 mu g kg(-1) CLO; adjusted to (3.4 + (body weight in kg x 0.013) mL with saline. Data were analysed by the Kolmogorov-Smirnov test, one-way ANOVA with repeated measures, and one-way ANOVA followed by a Student-Newman-Keuls test or Fisher's exact test, as necessary. Significance was set at p <= 0.05.Results Sedation and ataxia were seen at T10, persisting until T120 in four and three horses, respectively, in XYL and all horses in CLO respectively. Two XYL and one CLO horses became recumbent at T45 and T25 respectively. Penile prolapse occurred in four of five males at T30 and T45, in the XYL and CLO groups, respectively, resolving by T120. Tail relaxation was present from T10 to T120 in all horses in XYL and in four horses in CLO. Head drop was observed from T20 to T60 and from T10 to T120 in XYL and CLO respectively. Respiratory rate decreased significantly only at T45 in the CLO group. Heart rate and arterial blood pressure remained stable.Conclusions and clinical relevance Epidural CLO and XYL produce similar cardiorespiratory and behavioural changes but neither would be safe to use clinically at the doses used in this study.
Keywords: epidural clonidine; epidural xylazine; Horse